Endogenous Glucose Production Variation Assessment for Malaysian ICU Patients Based on Diabetic Status - Razak A.A.; Abu-Samah A.; Razak N.N.; Baharudin S.; Suhaimi F.M.; Jamaludin U. (Springer Science and Business Media Deutschland GmbH, 2023)
Biomedical engineering; Blood; Estimation; Insulin; Intensive care units; Physiological models; Stars; Stochastic models; Stochastic systems; Constant values; Control performance; Critically-ill patients; Diabetic patient; Endogenous glucose; Icing parameters; Insulin sensitivity; Small variations; Glucose